Review of Calotes versicolor an invasive lizard species on the island of Java - Pratiwi Restu Murti (PT. Gyandharma Global Media, 2026)
Calotes versicolor, or the oriental garden lizard, is a species of lizard native to South Asia and parts of mainland Southeast Asia. However, in recent decades, its distribution has expanded through human introductions to various archipelagic regions, including Indonesia. On the island of Java, C. versicolor is increasingly found in densely populated areas, agricultural areas, yards, and forest edges. This review article aims to examine the origins of C. versicolor in Java, potential introduction routes, factors for successful invasion, and its impact on local species and ecosystem structure. The method used is a desk study through a review of scientific literature from Google Scholar and online articles. The results of the study indicate that C. versicolor likely spread to Java through inter-island trade routes, agricultural transportation, and human movement routes from the colonial period to the modern era. This lizard's high habitat tolerance, effective reproduction, and opportunistic behavior make it a potential competitor to local lizards such as Bronchocela jubata, Eutropis multifasciata, and several native insect species. Ecological impacts include competition for space and food, predation on invertebrates and small vertebrates, and the potential spread of pathogens. This study emphasizes the importance of population monitoring and regional biosecurity policies to prevent the expansion of the impact of this invasive species in Java.